Mechanism of stapled peptide binding to MDM2 : possible consequences for peptide design - Sim, Adelene Y. L. (2015)
MDM2 is a negative regulator of p53. The N terminal domain of MDM2 interacts with a helical region of the transcriptional activation domain of p53. Stapled peptides have been designed to mimic this interaction, in order to inhibit p53-MDM2 binding and thereby activate the p53 response. Here, we studied how the helical segment of p53 or a stapled peptide (re)binds to MDM2 as it is systematically displaced from the MDM2 binding pocket. Depending on its sequence, presence of staple, and/or a C-terminal tail, the peptide approaches MDM2 differently and not exclusively via the crack propagation mechanism proposed previously for p53. The presence of an interacting staple appears to reduce the peptide’s sensitivity to mutations of key hydrophobic residues of p53, and this could pave the way for increased diversity in sequence design of stapled peptides used in inhibiting the p53-MDM2 interaction. We further found that the presence of a hydrophobic staple in the peptide-MDM2 interface tends to trap a network of water molecules prior to binding. The release of these structured waters would then reduce the entropic penalty upon peptide binding.